1996
DOI: 10.1073/pnas.93.21.11907
|View full text |Cite
|
Sign up to set email alerts
|

A novel clade of protistan parasites near the animal-fungal divergence.

Abstract: Sequences of nuclear-encoded small-subunit rRNA genes have been determined for representatives of the enigmatic genera Dermocystidium, Ichthyophonus, and Psorospermium, protistan parasites of fish and crustaceans. The small-subunit rRNA genes from these parasites and from the "rosette agent" (also a parasite of fish) together form a novel, statistically supported clade. Phylogenetic analyses demonstrate this clade to diverge near the animal-fungal dichotomy, although more precise resolution is problematic. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
123
2
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 170 publications
(136 citation statements)
references
References 33 publications
6
123
2
1
Order By: Relevance
“…The areas of the wedges reflect the number of SSU rRNA sequences of these groups in GenBank. The DRIP lineage is a recently defined protistan clade near the animal-fungal divergences (30). This figure is based on nonparametric bootstrap analyses of MP, ME, and ML trees, Bayesian inferences, and the analysis of alternative likelihood topologies of the novel lineages with the KH likelihood test in the PAUP* package (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…The areas of the wedges reflect the number of SSU rRNA sequences of these groups in GenBank. The DRIP lineage is a recently defined protistan clade near the animal-fungal divergences (30). This figure is based on nonparametric bootstrap analyses of MP, ME, and ML trees, Bayesian inferences, and the analysis of alternative likelihood topologies of the novel lineages with the KH likelihood test in the PAUP* package (see Table 1).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was not surprising that nSSU rDNA analyses (Benny and O'Donnell, 2000;Ustinova et al, 2000) indicated that Amoebidium was located within the DRIP's clade (an acronym of the organisms included in this clade: Dermocystidium, rosette agent, Ichthyophonus, and Psorospermium), a recently proposed clade near the Animal-Fungi divergence (Ragan et al, 1996). The DRIP's clade was identified as a novel class Mesomycetozoea (Herr et al, 1999;Mendoza et al, 2002).…”
Section: The Amoebidiales and Eccrinales Are Not Fungimentioning
confidence: 99%
“…One example is Thelohania contejeani (Henneg, 1892), that has caused mass mortalities of crayfish in Europe (Alderman and Polglase, 1988;Dunn et al, 2009;Edgerton et al, 2002). Another known disease is psorospermiasis, caused by Psorospermium (Mesomycetozoea) that colonizes gills, hepatopancreas, antennal gland, connective and neural tissues, ovary membranes and cardiac and skeletal muscle (Hennton et al 1994;Ragan et al, 1996;Longshaw, 2011).…”
Section: Trophic Ecologymentioning
confidence: 99%